Interpreting and Adapting a Digital Figure's Identity: A Qualitative Study of Generation Z Followers of @xavieraaputri on Instagram - Nurul Annisa Auliah Umar; Muh Akbar; Muhammad Iqbal Sultan; Aqilah Aliefia Syahrani (LONTAR: Jurnal Ilmu Komunikasi, 2026)
This study examines how Generation Z followers of the Instagram account @xavieraaputri interpret, negotiate, and selectively adapt the mediated self-presentation of a digital figure into their own identity strategies on Instagram. Using a qualitative case study approach, data were collected through in-depth interviews, observation, and documentation. The findings reveal that informants perceive the account as a representation of authentic identity, displaying a balance between achievements, processes, and vulnerability, which in turn triggers reflection in constructing their own identities. The interpretive-adaptive process is manifested across three dimensions: frontstage, backstage, and impression management. In the frontstage, informants shift their focus from mere aesthetics toward meaningful content that reflects personal values. In the backstage, they consciously limit private aspects as a form of self-protection, relational boundaries, and preservation of personal values, functioning not as concealment of a singular “true self” but as context-specific negotiation of visibility. In impression management, informants weigh professional, social, religious, and personal considerations before uploading content. The findings indicate that the digital figure acts as a catalyst for vicarious learning rather than a determinant of behavior, meaning that identity construction results from the selection and adaptation of relevant values rather than imitation. This study extends Goffman's dramaturgical framework by showing that performance repertoires can be acquired through observation of a distant figure's mediated, asynchronous performance, a mechanism not accounted for in Goffman's original interactional model.